Analisis Kelayakan Finansial Usaha Hidroponik di Kelurahan Kambu Kecamatan Kambu Kota Kendari (Studi Kasus Hidroponik Faperta) - Boer, Nilam Permatasari; Abdi, Abdi; Gafaruddin, Abdul (Department of Agribusiness, Halu Oleo University, 2021)
This research investigates the hydroponic business's revenue, analyzes the financial feasibility of a hydroponics business, and analyzes the sensitivity of the economic feasibility of a hydroponic business in Kambu Village, Kambu Sub-district, Kendari City (Studi Case: Hidroponik Faperta). This study aims to find out whether several factors could influence profits and prices in the business. This research was conducted in Kambu Village, Kambu Sub-district, Kendari City, from January 2020 to July 2020. The subject of this research is Hidroponik Faperta. This research uses the study case method. The data analyzed by the researcher is Financial Feasibility Analysis which includes as follows: Net Present Value Analysis, Net Benefit-Cost Ratio Analysis, Internal of Return Analysis, Payback Period Analysis, and Sensitivity Analysis. The results of this study obtained revenue in the first year of this business suffered a loss of Rp.6.438.600,- and in the second year revenue of Rp.175.032.000,-. The result of this research shows that there was also NPV of Rp.70.817.139,- obtained with a discount factor of 20%, Net B/C of 2,16, IRR of 96,8%, the Payback period for one year, four months, and seven days. The financial aspect analysis result could be summarized that business is feasible. Therefore, as the conclusion, this business is still feasible, despite a 15% decrease in vegetable production and 10% increase in seeds prices and hydroponic nutrition prices, each up 10% based on the calculation of the sensitivity analysis